As performances discursivas e as ordens de indexicalidade de gênero, raça e sexualidade no desabafo de uma mulher negra veiculado no YouTube - Silveira, Romilda Pinto da (2016)
According to Giddens (1991), Reflexive Modernization is a moment of reflexivity about ourselves, a defining characteristic of human action in the social practices and in the bodies considered abject traditionally legitimized by modernist ideals. This research aims to analyze the discursive performances of race, gender and sexuality in an outburst recorded by a black woman, posted on YouTube channel with the purpose of criticizing a television miniseries entitled "Sex and the Niggaz". It also proposes to specifically identify indexicality orders of race, gender and sexuality mobilized in the discursive performances of Dandara. In this study, we chose the video of a black woman, a lawyer from the middle class because, according to data from IBGE (Brazilian Institute of Geography and Statistics), there are few black women occupying key positions, for which they earn the worst market wages since they are at the lowest possible level of the social pyramid (MELO; MOITA LOPES, 2013). In order to conduct this research, we consider language as performative speech acts in the perspective of Austin (1962) and Derrida (1972), who claim that in uttering, one produces. Moreover, Derrida adds that the performative speech acts gain the idea of substance by iterability and citationality. We also based ourselves in the conceptions of race, gender and sexuality as social, historical, discursive and performative constructs, according to Queer Theories (LOURO, 2000; BUTLER, 1990/2014; BARNARD, 2004; MELO; MOITA LOPES, 2013). As regards to methodology, theoretical and analytical construct is anchored to the concept of indexicality order proposed by Blommaert (2010), and the data generation material is the outburst of Dandara, in video form, broadcasted on YouTube. For the analysis of discursive performances and indexicality orders of Blommaert (2010), we resorted to using the linguistic indexes suggested by Silverstein (1985), which included the categories of Wortham (2001). This research points to several discursive performances, such as, successful black woman challenging stereotypes that depreciate black women. It also mobilizes several indexicality orders, such as: prestigious profession, references that make the black woman inferior, positive representation of black women.